(untitled) (Global Journal of Science Frontier Research, 2015)
Innovation and technology are important catalyst in wealth creation and development of societies and nations. Progress in science is advanced by dissemination of know-how, whether by original innovation or by reverse engineering of existing technology. While original innovation is the standard in this regard, the open secret to boosting economic growth has been said to be reverse engineering, which basically involves the creation of inventions and innovations from the study of existing technology. Reverse engineering is said to lead to faster development and innovations as the creations are based on an existing design and less time and fund is spent on trial and error while working on original inventions. China is one of many nations that discovered this well kept open secret decades ago and are currently harvesting the benefits of its use. It has used reverse engineering to rise and transform itself from a developing nation to one of the largest economies in the world, with the highest economic growth rate in the world today. Nigeria, on the other hand can at best be described as a new born, where reverse engineering for economic growth is concerned.